Is roof-top rainwater harvesting a viable solution to develop small-scale agriculture? (A case study in Laos) - Jacq, Estelle; Lacombe, Guillaume; Heang, Vytou; Douangsavanh, Somphasith (2018)
This study assessed the feasibility of using roof-top rainwater harvesting system (RWHS) to irrigate home-based vegetable gardens in Laos. Surveys were conducted in three villages located in the provinces of Vientiane and Savannakhet to gather quantitative data on irrigation and farming practices. A model combining a RWHS water balance and a crop water balance was developed to simulate various scenarios of cropping cycles irrigated by a RWHS with varying dimensions. This model ran at a daily time step aimed to assess how the roof and vegetable garden areas and tank capacity influence crop yields, for different cropping calendars and rainfall years.